PENGARUH MANFAAT DAN KEMUDAHAN TERHADAP KEPUASAN NASABAH MOBILE BANKING DI BANK BRI SYARIAH - Teti Anggita Safitri (JURNAL LENTERA BISNIS, 2023)
Sharia investment as an investment that is in accordance with the principles of islamic economics is an investment that does not contain elements of usury. it is hoped that by applying sharia investment principles one can invest without violating religious norms. one form of sharia investment is investment in sharia banking. islamic banks are the people's choice because they stay away from usury, besides that islamic banks apply the principle of profit sharing because they collect public funds through savings and deposits. Bank bri syariah is a bank that applies sharia principles that has access to mobile banking for its customers, so that with mobile banking it can make it easier for bri syariah bank customers to make transactions, where the use of mobile banking is a form of sharia financial technology that cannot be separated from community activities. therefore, this study aims to explore the convenience and benefits of islamic financial technology in using mobile banking for customers.Based on the results of the research that has been done, it can be concluded that 1). the effect of benefits on mobile banking customer satisfaction is partially indicated by a significance level of 0.008 less than 5% so that h1 is accepted; 2). the effect of convenience on satisfaction using mobile banking is partially indicated by a significance level of 0.018 less than 5%, so h2 is accepted.Key Words: Financial Technology, Sharia, Mobile Banking